An Analysis of Neurosis Need of Veronika Character in “Decides to Die” Movie - Warno Edi; Harmiati Harmiati (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
This research aimed to determine the causes of depression experienced by the main character of the “Decides to Die”Movie with used theory have been raised by the professional. The causes of depression was a problem in the family as well as the encouragement depression as a factor in alcohol abuse, drug abuse, hormonal change thought and behaviours. The purpose of this research was to analyze the causes of depression of the main character of “Decides to Die”movie. This research was used on the theory psychological approach. This research explained the main character named Veronika began to depression caused because of a problem in a relationship marriage her husband affair with another woman without the knowledge of Veronika because she is busied worked. Finally, Veronika experienced depression began to consume the drug, and also consumed alcohol and finally she thought wanted to end her life. As a conclusion, based on movie script and scene through Kenneth B Wells psychological approach theory, the causes depression of the Veronika the first is caused there was a third person in Veronika household, the second consumes many drug and induced with dependence the drug and Veronika also consume a bottle alcohol  that can increase her life is not controlled. The last is thought of Veronika want try to die,and behaviour of Veronika was hated all the people and belonged her parents.